Tinjauan Fiqih Waris Islam Terhadap Anak Angkat Menggunakan Pendekatan Normatif - Darmawan, M. Ilham; Rizki, Muhammad; Nadilah; Antyesti; Putri, Meli Anggraini; Vidyasari, Vivid; Sari, Jeni Permata; Noviani, Dwi (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study examines the Islamic fiqh perspective on the status of adopted children in inheritance distribution using a normative approach, focusing on the analysis of rules and legal proofs from the Qur'an and Hadith; in Islam, adopted children do not automatically have inheritance rights because there is no biological lineage, thus solutions such as gifts (hibah) or wills are needed to ensure adopted children receive 2 a fair share without violating Islamic inheritance principles, which emphasize justice, social balance, and the preservation of family values, while demonstrating how Islamic inheritance law systematically accommodates humanitarian values and family harmony even when blood ties are absent